Strategi Public Relations Pt Paragon Technology And Innovation Dalam Mempertahankan Brand Loyalty Di Pasar Kosmetik Surabaya - Hananda Dyan Ekawatie; Muhammad Fadeli; Ratna Setyarahajoe (CV. ITTC INDONESIA, 2026)
The cosmetics industry in Surabaya is currently facing intense competition and challenges related to illegal products. However, PT Paragon Technology and Innovation has managed to maintain consumer loyalty by implementing a comprehensive Public Relations strategy through community engagement, digital PR, and the creation of brand experiences. This Public Relations strategy serves as a key element that functions not only as a promotional tool but also to build long term trust with consumers. This study aims to analyze Paragon's Public Relations strategy in maintaining brand loyalty within the Surabaya cosmetics market using a descriptive qualitative research method, with data collection techniques including in depth interviews with the promoter team and consumers, participant observation at various brand activations, and documentation. The most compelling aspect of this research is the use of interactive tactics such as Personal Color Analysis services and creative DIY product making workshops, as well as strategic collaborations with communities and influencers who share the same brand values. This strategy is proven effective in building four relationship dimensions trust, commitment, satisfaction, and mutual interest which are capable of transforming impulsive buying behavior into strong loyalty. It is suggested that further research explore the influence of this strategy on broader market segments.